Implementation of Android-Based Learning Media with Ethnomathematical Approach Batik Nusantara - Nur Ika Adila Rahmawati; Joko Soebagyo (Budapest International Research and Critics University, 2022)
This study aims to determine the feasibility of Android-based mathematics learning media with an ethnomathematical approach to eighth grade junior high school students. introduce the nation's culture to students who are integrated in learning mathematics. This research is research on the R&D development model of ADDIE. Research and Development Methods are oriented towards product development where research processes and procedures are carefully described and then evaluated to determine the level of effectiveness. The stages of developing this model are Analysis, Design, Development, Implementation, and Evaluation. however, in this study, it was only used until the development stage. In the analysis stage, a needs analysis was carried out to see the situation in the field related to the teaching and learning process carried out by interviewing educators and students. The design stage designs the initial product to be raised. Starting from ensuring the design of educational media, which will be raised to meet the feasibility of consumption in accordance with the modules presented, and collecting data from various reference sources from existing research or media. At the development stage, the features developed are tested so that they can be used as much as possible.